The Others: Social Distance between North Macedonian and Albanian Students - Langher, Viviana; Georgievska, Sofija; Ajdinski, Goran (Nova Publisher, New York, 2019)
“Ethnic distance” is the social distance between different ethnic groups. It influences the acceptance/rejection of members of different ethnic groups in personal and social relationships. It affects intergroup attitudes, willingness to connect with various ethnic groups, and general social behavior. This chapter discusses research regarding social distance for students of North Macedonian and Albanian ethnic origins. The study was carried out on convenience samples of students from high schools and universities. The results converge on the finding of auto- and hetero-stereotypes, underlining the existence of social distance between the two groups. The results highlight the local culture in North Macedonia, its impact on the quality of social relationships between the two groups, and its possible negative effect on the country’s social development. The role of a separate, language-based educational system is discussed.
Keywords: social distance, interethnic attitudes, North Macedonia, semantic differential